2015
DOI: 10.1109/tap.2015.2405077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonuniform Surface Errors Along the Radius on Reflector’s Radiation Characteristic and Its Quality Evaluation

Abstract: Based on the works of Yahya Rahmat-Samii, a multiobjective optimization model is developed to analyze the effects of surface errors' nonuniformity along the radius on the reflector's radiation characteristic. Through the optimization model, Pareto front for trading off the peak gain loss (PGL) and the first sidelobe level increase (SLLI) is obtained. Simulations clearly show that for the same root mean square (rms) error for the whole reflector, different distributions along the radius result in different PGLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…It should be noted that the correctness of had been demonstrated in our previous works, and the results showed that there was good agreement for the main beam and for several side lobes near the main beam between the measured data and simulation data. In fact, many researchers have adopted to calculate the reflector's EM performance in their research papers …”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the correctness of had been demonstrated in our previous works, and the results showed that there was good agreement for the main beam and for several side lobes near the main beam between the measured data and simulation data. In fact, many researchers have adopted to calculate the reflector's EM performance in their research papers …”
Section: Formulationmentioning
confidence: 99%
“…However, the misalignment errors mentioned in Reference refer to the feed displacements and the translations and rotations of the entire reflector. In our previous works, the effects of nonuniform surface errors along the radius were considered in terms of electromagnetic performance, but the PIEs were different from the random surface errors presented in References 18 and 19. In References 20 and 21, the relationship between the PIEs and the aperture phase errors was derived and their effects on the power pattern were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, a large aperture can result in large gravitational deformation, and the telescope can also become more sensitive to inevitable external environmental impacts, such as temperature and wind [2][3][4]. Numerous research papers have analysed the effect of the surface deformation of a radio telescope on its electromagnetic performance [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Duan and Wang [12] studied the influence of surface random errors and systematic errors on the EMP and established an optimization model for the integrated mechanical-electromagnetic performance. Lian et al [13] developed a multiobjective optimization model to analyze the effects of surface errors' nonuniformity along the radius on the reflector's radiation characteristic and discussed that for the same RMS of errors for the whole reflector, different distributions along the radius result in different gain losses and sidelobe levels. However, these works consider only one type of error distribution, such as the variations in radial or azimuthal directions, and hence, they cannot represent all situations that influence of the arbitrary error distributions.…”
Section: Introductionmentioning
confidence: 99%